2001
DOI: 10.1351/pac200173030613
|View full text |Cite
|
Sign up to set email alerts
|

Molecules and macromolecules involved in chemical communication of scarab beetles

Abstract: Chemical communication involves the production and release of specific chemicals (pheromones and other semiochemicals) by the emitter, and the detection and olfactory processing of these signals leading to appropriate behavioral responses in the receiver. In contrast to most of the scarab species investigated to date, the Japanese and Osaka beetles have the ability to detect the allospecific pheromone, which plays a pivotal role in the isolation mechanism between these two species. Each species produces a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Also, among other Pleurosticts (i.e., the paraphyletic "Melolonthinae", Cetoniinae, and Rutelinae), there are some quite speciespoor lineages and slowly diverging lineages with "modern" sensilla (Table 1). Hence, we see the here presented hypotheses and results as a starting point to refine our phylogenetical understanding of the Scarabaeoidea but most of all to open up for a molecular characterization of antennal sensilla functionality, regarding pheromones and odor binding proteins of sensilla (e.g., Leal 2001;Nikonov et al 2002;González-González et al 2019) to improve our understanding of their chemical communication, ecology and evolution.…”
Section: Discussionmentioning
confidence: 92%
“…Also, among other Pleurosticts (i.e., the paraphyletic "Melolonthinae", Cetoniinae, and Rutelinae), there are some quite speciespoor lineages and slowly diverging lineages with "modern" sensilla (Table 1). Hence, we see the here presented hypotheses and results as a starting point to refine our phylogenetical understanding of the Scarabaeoidea but most of all to open up for a molecular characterization of antennal sensilla functionality, regarding pheromones and odor binding proteins of sensilla (e.g., Leal 2001;Nikonov et al 2002;González-González et al 2019) to improve our understanding of their chemical communication, ecology and evolution.…”
Section: Discussionmentioning
confidence: 92%
“…31 Por lo general, en insectos, la percepción del olfato se realiza a través de sensilias especializadas con receptores olfatorios (ORs) en las antenas. 187 En la ecología química existen distintos tipos de bioensayos que favorecen la identificación como semioquímicos de compuestos orgánicos volátiles identificados en los sistemas de estudio. Entre estos se encuentran aproximaciones electrofisiológicas tales como las técnicas de electroantenografía (EAG) que pueden ser independientes o acopladas como detectores a técnicas de separación por cromatografía de gases (GC-EAD).…”
Section: Antecedentesunclassified
“…This and the observation that a number of OBPs, including BmPBP, do not bind ligands below pH 5.0 (8,9) suggests that pH variation of the folded conformation might play a physiological role in olfaction (10,11). In this context, it is intriguing that near-UV circular dichroism measurements revealed that BmPBP undergoes a conformational transition when mixed with model membranes (12).…”
mentioning
confidence: 99%